Novel insights on targeting ferroptosis in cancer therapy - Sipeng Zuo; Jie Yu; Hui Pan; Linna Lu (BMC, 2020)
Abstract Ferroptosis belongs to a novel form of regulated cell death. It is characterized by iron dependence, destruction of intracellular redox balance and non-apoptosis. And cellular structure and molecules level changes also occur abnormally during ferroptosis. It has been proved that ferroptosis exist widespreadly in many diseases, such as heart disease, brain damage or alzheimer disease. At the same time, the role of ferroptosis in cancer cannot be underestimated. More and more indications have told that ferroptosis is becoming a powerful weapon against cancer. In addition, therapies rely on ferroptosis have been applied to the clinic. Therefore, it is necessary to understand this newly discovered form of cell death and its connection with cancer. This review summarizes the mechanism of ferroptosis, ferroptosis inducers based on different targets and inspection methods. At last, we analyzed the relationship between ferroptosis and malignancies, in order to provide a novel theory basis for cancer treatment.